(untitled) (Clinics, 2011)
OBJECTIVE: The purpose of this study was to investigate the correlation between body adiposity and postural control in elderly women. INTRODUCTION: Aging and obesity account for a significant portion of healthcare spending. Life expectancy is increasing worldwide, and Rio de Janeiro has the largest proportion of elderly residents of all Brazilian states. METHODS: A total of 45 women underwent bioelectrical impedance analysis, waist circumference measurements, weight and height measurements, and stabilometric tests in eight different stance conditions (opened and closed bases with both eyes opened and closed and right and left tandem and unilateral stances with eyes opened). During unilateral stances, the number of hand or foot contacts was counted. RESULTS: Weight, body mass index, waist circumference, fat percentage, and fat mass showed statistically significant (p,0.05) and positive correlations with the number of contacts made during unilateral stances. The subjects with greater fat mass showed significantly higher anterior-posterior standard deviation and range when their eyes were closed. The sway area was also greater for this group in opened base when their eyes were closed. DISCUSSION: The results relating body adiposity and postural control can be explained by the difficulty of maintaining a greater quantity of body fat mass within the limits of the individual support base, especially while assuming a unilateral stance. CONCLUSION: The subjects with a greater fat mass exhibited poor balance control, indicating that body adiposity level was associated with postural control in the elderly women examined in the present study.